THE ANALYSIS OF EDUCATION POLICIES AND THE IMPACT OF COVID 19 ON EDUCATION INSTITUTIONS IN INDONESIA - Junaidi, Akh; Ansori, Ansori (IKIP Siliwangi Bandung, 2025)
Large-scale Social Restrictions taken as a policy of the Republic of Indonesia's government to break the chain of Covid-19 spread have had a major impact on teaching and learning activities in all educational institutions in Indonesia. In this difficult condition, of course, the role of educational institutions as a learning platform for all levels of society must continue to run optimally to support national development. Steps were taken by educational institutions as an alternative in implementing learning such as online-based distance learning and assignments or home projects. This study aims to analyze the policies taken by the central government in the realm of education and to determine the impact of Covid-19 on educational institutions in Indonesia. The method used in this research is descriptive with documentation study data collection techniques